The Italian Madrigal : Volume II - Einstein, Alfred, 1880-1952 (Book collections on Project MUSE., 2019)
Volume 1 of 3. This monumental three-volume work on the Italian madrigal from its beginnings about 1500 to its decline in the 17th century is based on the research of 40 years, and is a cultural history of the development of Italian music. Mr. Einstein, renowned musicologist, supplies a background and a sense of proportion to the field: he gives the right order to the single composers in the evolution fo the madrigal, attaches new values to old names, and places in the foreground the outstanding, but until now rather neglected, personality of Cipriano de Rore. His work is not, however, purely musicological; his object is to inquire into the functions of secular music in Italian life during the Cinquecento, and to contribute to our knowledge and understanding of that great century in general. Translated from the German by Oliver Strunk, Roger Sessions and Alexander H. Krappe. Originally published in 1948. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.